Consumption of durable goods under ambiguity - Othón M. Moreno (Banco de México, 2014)
The focus of this paper is to analyze the effect that ambiguity will have on the buyer's reservation price and the value of the option to purchase the durable good with an embedded option to resell it. The agent is assumed to be risk neutral and ambiguity averse. The problem is formulated as an optimal stopping problem with multiple priors in continuous time with infinite horizon. Uncertainty comes from prices, which is summarized in a state variable that follows a Brownian motion. Preferences have a multiple-prior utility representation where the set of priors consist of a family of Brownian motions with unknown drift and common variance. We show that the direction of the change in the buyer's reservation price depends on the parametrization of the model and that the value of the embedded option is decreasing in the perceived level of ambiguity.
Keywords: C61; D81; D91; 330; ambiguity; optimal stopping; embedded option; durable goods